Body Care as an Effort to Improve Beauty and Health for Post Partum Mothers in Lamongan Regency, East Java, Indonesia - Sari, Ponco Indah Arista (International Journal of Natural and Health Sciences, 2024)
Pregnancy, childbirth and breastfeeding are natural and physiological processes for every woman who plays the role of a mother. The end of this quite long process is the birth of a baby which the parents have been waiting for. After the baby is born with the placenta, it will be the peak of adaptation for a mother and her baby. The mother will enter the postpartum and breastfeeding period where the mother will assume her new role. Some of these discomforts will bother the mother and cause increased morbidity in the mother. The World Health Organization (WHO) recommends that health care during the postpartum period can be started 24 hours after giving birth or when the mother is in a physiological postpartum state. This treatment can be carried out by competent personnel such as doctors, midwives or nurses. This health care is an effort to improve the level of health as a mother in general and during the postpartum period and breastfeeding in particular. From this adaptation process you will find some discomfort. This can be overcome with postpartum care. The research method used is descriptive quantitative. Using the total population, from the cross tabulation results, 65.7% of postpartum mothers who underwent postpartum care were in a healthy condition during the postpartum period (42 days). These results show that there is a tendency for mothers who undergo postpartum care to have a healthy body condition. From this, it becomes a reference that postpartum care is very important for postpartum mothers to be able to improve the mother's health status during the postpartum period and beyond